Empowering lead users: Kenya’s three-part formula for fintech innovation success - Otieno, Geoffrey; Kiraka, Ruth (Serbian Journal of Management, 2025)
Lead user innovation is one of the key factors which define new product development and market success, but the characteristics of user innovators in emerging markets are still not explored enough. This research aims at finding out the effect of work experience, autonomy and number of partners in innovation on success of lead user innovation in Kenya’s Fintech industry. The quantitative data was collected through a survey of 321 lead user innovators while qualitative data was collected through 36 in-depth interviews. This analysis demonstrates that work experience has an influence on success through innovation partners and indirectly through the work experience, which has an influence on success directly through autonomy but has no indirect impact on success through partners. Thus, the study adds to the body of literature on user innovation by identifying factors that are essential for success in an emerging market and by providing recommendations for organizations that encourage user-driven innovation. The emphasis on the Kenyan fintech segment and the consideration of the mediating roles of innovation partners contribute to the novelty of innovation research. The results also highlighted the fact that the key factors influencing lead user innovation success are work experience, autonomy, and collaboration.